Towards an integration of biodiversity-ecosystem functioning and food web theory to evaluate relationships between multiple ecosystem services - Hines, Jes; van der Putten, Wim H.; De Deyn, Gerlinde B.; Wagg, Cameron; Voigt, Winfried; Mulder, Christian; Weisser, Wolfgang W.; Engel, Jan; Melian, Carlos; Scheu, Stefan; Birkhofer, Klaus; Ebeling, Anne; et al. (Advances in ecological research, 2015)
Ecosystem responses to changes in species diversity are often studied individually. However, changes in species diversity can simultaneously influence multiple interdependent ecosystem functions. Therefore, an important challenge is to determine when and how changes in species diversity that influence one function will also drive changes in other functions. By providing the underlying structure of species interactions, ecological networks can quantify connections between biodiversity and multiple ecosystem functions. Here, we review parallels in the conceptual development of biodiversity- ecosystem functioning (BEF) and food web theory (FWT) research. Subsequently, we evaluate three common principles that unite these two research areas by explaining the patterns, concentrations, and direction of the flux of nutrients and energy through the species in diverse interaction webs. We give examples of combined BEF-FWT approaches that can be used to identify vulnerable species and habitats and to evaluate links that drive trade-offs between multiple ecosystems functions. These combined approaches reflect promising trends towards better management of biodiversity in landscapes that provide essential ecosystem services supporting human well-being.